2018
DOI: 10.1002/bmc.4444
|View full text |Cite
|
Sign up to set email alerts
|

Microextraction sample preparation techniques in forensic analytical toxicology

Abstract: Sample preparation is a critical step in forensic analytical toxicology. Different extraction techniques are employed with the goals of removing interferences from the biological samples, such as blood, tissues and hair, reducing matrix effects and concentrating the target analytes, among others. With the objective of developing faster and more ecological procedures, microextraction techniques have been expanding their applications in the recent years. This article reviews various microextraction methods, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 90 publications
(89 reference statements)
0
18
0
3
Order By: Relevance
“…Sample pH is an important parameter in techniques involving analyte partition between aqueous and organic phases, such as DLLME. This factor is optimized according to the analyte, where basic compounds require a high pH to be maintained in the non‐ionized form to dissolve in the droplets of extractor solvent . TQ has basic characteristics (p K a = 10.20) and, therefore, it is expected that a basic medium should facilitate extraction from biological samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample pH is an important parameter in techniques involving analyte partition between aqueous and organic phases, such as DLLME. This factor is optimized according to the analyte, where basic compounds require a high pH to be maintained in the non‐ionized form to dissolve in the droplets of extractor solvent . TQ has basic characteristics (p K a = 10.20) and, therefore, it is expected that a basic medium should facilitate extraction from biological samples.…”
Section: Resultsmentioning
confidence: 99%
“…The dispersive solvent must be miscible in the sample (aqueous phase) and in the extractor solvent (organic phase) in order to yield a ternary system, which will concentrate analytes in extractor solvent. The mixture obtained by the rapid injection of extractor and dispersive solvents in the sample promotes the dispersion of droplets with high superficial area, in which fast partition occurs . Considering its advantages over traditional techniques of sample preparation, several methods have been reported using this approach lately.…”
Section: Introductionmentioning
confidence: 99%
“…Their selectivity enables substantive removal of matrix interferents during the sample pre-treatment step [119]. MIP-based sorbents are readily available substitutes to silica-based adsorbents, which are reported to suffer from matrix interference, low selectivity, and sensitivity towards organic pollutants and may involve multiple steps that are labour-intensive for complete removal of interferences [120]. For example, commercial molecularly imprinted solid-phase extraction (MISPE) cartridges alongside alkaline extraction have been applied in aqueous enrichment and quantitation of PBDEs using GC-MS [121].…”
Section: Advances In Spe Sorbentsmentioning
confidence: 99%
“…This solvent fills the pores of the HF, after which the inner lumen of the hollow fiber is filled with an acceptor solution. The HF is placed in the sample and extracts the analytes from the sample (Gjelstad & Pedersen-Bjergaard, 2013;He & Concheiro-Guisan, 2019). Recently, it was shown that by modifying HF with sorbents that they can be used for solid-phase microextraction, thereby combining SPME and LPME which is named solid-liquid-phase microextraction (SLPME) (Yang, Chen, & Shi, 2015).…”
Section: Microextractionsmentioning
confidence: 99%
“…Extraction techniques are classified as a microextraction if the volume of the extracting phase is very small in relation to the volume of the sample. (He & Concheiro‐Guisan, ). Based on the extraction phase a microextraction method can be classified as solid‐phase microextraction (SPME) or liquid‐phase microextraction (LPME).…”
Section: Sample Pre‐treatmentmentioning
confidence: 99%